Inovasi Sistem Kontrol Elektronik Berbasis Arduino untuk Proses Penekanan Adonan Kue Tradisional - Saukani, Imam (Elposys: Jurnal Sistem Kelistrikan, 2024)
The aging of Traditional production of Onthok Yuyu, a local delicacy, encountered challenges in efficiency and consistency due to its manual process, which affected the product’s uniformity and overall productivity. This study aimed to design and implement an automated dough-cutting system using an Arduino Uno-based controller combined with Pulse Width Modulation (PWM) to address these issues. The system used an Arduino Uno to manage motor speed and cutting precision, utilizing a programmable keypad for setting time intervals and controlling dough compression and cutting stages. The experimental setup included a DC motor to drive the cutting blades, a conveyor motor, and a display for real-time process monitoring.Key findings revealed that the automated system achieved consistent cutting lengths with minimal variance, improving both the efficiency and reliability of the production process compared to traditional methods. The system effectively managed motor speed within specified parameters, resulting in uniform dough portions while reducing manual labor. Additionally, the study showed that the Arduino-controlled setup maintained operational stability under various loads, making it adaptable for small-scale production.This research demonstrated the potential for Arduino-based automation to enhance production quality in traditional food processing. It offers implications for similar small and medium-sized enterprises (SMEs) aiming to modernize processes, reduce dependency on manual labor, and achieve more consistent output. Future studies are recommended to explore further optimization in system scalability and adaptability for diverse product types